Towards an Ethical Research Agenda for International HRM: The Possibilities of a Plural Cosmopolitan Framework - Janssens, Maddy 1959-; Steyaert, Chris 1962- (2012)
In this conceptual paper, we aim to develop a much needed ethical research agenda for international Human Resource Management (HRM), given that the changing geopolitical dynamics interrogate the political role of multinational companies and the ethical stance they take in their HRM practices. To theoretically ground this agenda, we turn to cosmopolitanism and distinguish three main perspectives—political, cultural, and social—each of which implies a different understanding of the self–other relation in the context of the global world. We translate the core and ethical stance of each perspective to the field of international HRM, presenting three different foci of an ethical research agenda in terms of the ethical implications for multinational companies, research focus, methodological suggestions, and inherent limitations.
Keywords: Ethics; Cosmopolitanism; International HRM